Om ordbokskriminalitet og etikk i leksikografisk arbeid - Fjeld, Ruth Vatvedt (LexicoNordica, 1994)
The discussion of decent behaviour in lexicography can be divided into two fields, criminality and ethics. Cåminality is here defined as what is forbidden by law, e.g. to break the rules of copyright. Ethical problems occur in the area between what is legal and what is allowed, where there will always be a vague zone. There are two main fields to be considered: who has the right to standardize other people’s language, to decide what is an accepted word, and what is not, and how to decide what the words mean? The other problem concerns stealing others’ work, the well-known subject of plagiarism.